PENGEMBANGAN HUKUM ISLAM (FIQH) MELALUI PENDEKATAN MAQASID AL-SYARI’AH, KELEBIHAN DAN KEKURANGANNYA - Ahmad Yusuf; Mirza Mahbub Wijaya (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
This research is a literature study which tries to explore the concept of maqasid al-syariah. Basically, syari'at and religion cannot be understood partially. However, it must be viewed as a whole as an inseparable entity. Religious goals and shari'ah goals can be categorized into general goals and specific goals. The general objective in general is not different from all religious and insaniyyah teachings. Fiqh / fiqh proposal will be more relevant if it is based on socio-cultural context. In other terms, fiqh is an authority that can be accepted by all space and time. This can be realized if jurisprudence experts and all Muslims have a mindset that is open to other scientific fields which of course will be able to realize the condition of rahmatan li al alamin.